Dark to Meet Light. Claudio Magris’s Blameless and the Struggle against Oblivion - Fruner, Sara (Testo e Senso, 2020)
New York City can be generous in unexpected ways. In April 2017, Italian master writer and maître à penser Claudio Magris was invited at the Italian Cultural Institute to launch Blameless, the English translation of his 2015 novel Non luogo a procedere. No nobody introduced Magris that evening. Romanian major writer Norman Manea, both an admirer and a dear friend of the Italian author, was there to moderate the conversation and to bring his own perspective to the novel and to his work. Having Romania’s and Italy’s most likely candidates for the next Nobel Prize in Literature in the same room, talking about their art and life, is a gift that fills one with the utmost delight.